Communication Experiences in Primary Healthcare with Refugees and Asylum Seekers: A Literature Review and Narrative Synthesis - Patel, Pinika (Int J Environ Res Public Health, 2021)
Refugee and asylum seeker population numbers are rising in Western countries. Understanding the communication experiences, within healthcare encounters, for this population is important for providing better care and health outcomes. This review summarizes the literature on health consultation communication experiences of refugees and asylum seekers living in Western countries. Seven electronic databases were searched from inception to 31 March 2019. Studies were included if they aimed to improve, assess or report on communication/interaction in the primary health care consultation setting with refugees or asylum seekers, and were conducted in Western countries. A narrative synthesis of the literature was undertaken. Thematic analysis of the 21 included articles, showed that refugees and asylum seekers experience a range of communication challenges and obstacles in primary care consultations. This included practical and relational challenges of organizing and using informal and formal interpreters and cultural understanding of illness and healthcare. Non-verbal and compassionate care aspects of communication emerged as an important factor in helping improve comfort and trust between healthcare providers (HCP) and refugees and asylum seekers during a healthcare encounter. Improvements at the systems level are needed to provide better access to professional interpreters, but also support compassionate and humanistic care by creating time for HCPs to build relationships and trust with patients.